Age-related immune-modulating properties of seminal fluid that control the severity of asthma are gender specific - Niikura, Yuichi; Ishii, Takashi; Murakami, Jurika; Narita, Tomoya; Fujita, Yoko; Negishi, Hiroaki; Taketani, Yuji; Yamashita, Naomi (Aging (Albany, NY.), 2019)
Reproductive organs play a pivotal role in asthma development and progression, especially in women. Endocrine environment changes associated with the menstrual cycle, pregnancy, and menopause can exacerbate the clinical features of asthma. Factors secreted by reproductive organs may be responsible for the gender difference and age-related changes in adult asthma. Here, we show that mammalian seminal fluid has anti-asthma effects exclusively in females. Exposure to murine seminal fluid markedly reduced eosinophilic airway inflammation in 2-month-old female mice upon ovalbumin inhalation. The anti-asthma effect with seminal fluid from 10-month-old males was double that with fluid from 2-month-old males, suggesting that it depended on male sexual maturation. We further found that seminal fluid from middle-aged human volunteers had beneficial effects in asthmatic female mice; these effects were associated with transcriptional repression of osteopontin and IL-17A, which are poor prognostic factors for asthma. In 2-month-old male mice, however, human seminal fluid failed to decrease asthmatic features and even enhanced osteopontin and IL-17A transcription. Our data demonstrate that age-related seminal fluid exerts opposing effects in asthmatic male and female mice. These findings may help the development of novel approaches to control the prevalence and age-related progression of asthma in women.